On graphic intent, a perambulation - Ramos, M. (Drawing heritage(s), 2021)
This text deals with intentionality in in situ drawing, on two dimensions: that of its actual practice and that of its public sharing. Taking as example a brief and constrained situational observational group sketching experiment in a landscape with elements of recognisable heritage status, it discusses the means through which these dimensions become intertwined, and reflects on the limited worth of ideologically-framed categorisations - such as the divide between tangibility and intangibility of cultural values - to elucidate how drawing is a knowledge-driven endeavour.